Public Buildings and Trafalgar Square with War Memorial, Barbados, B. W. I. - Ltd., Knight’s (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2022)
This picture displays Public Buildings and Trafalgar Square with War Memorial in Barbados, British West Indies. Two horse-drawn carts on the street and the waterfront in the foreground are also visible. Info. At the back: Published by Knight’s Ltd. Barbados Printed in Saxony AL INT £4.50
Landscape, black & white, 4 x 6 in., divided back
Keywords: Buildings; Boats; Cityscapes; Historic buildings; Historic sites; Public Buildings; Trafalgar Square; War Memorial; Careenage; Parliament Buildings; Knight's Limited